Recent advances on fabrication of microneedles on the flexible substrate. (9th June 2021) - Huang, Dong; Li, Junshi; Li, Tingyu; Wang, Zhongyan; Wang, Qining; Li, Zhihong
Abstract: Microneedles are able to penetrate into the skin and offer great chances in various biomedical applications including transdermal drug delivery, stable bio-signal monitoring, sampling and bio-sensing. Owing to the micro-scale feature size, microneedles have advantages of minimal invasiveness, pain, high biosafety and simple operation. However, it is still challenging to fabricate solid microneedles on a flexible substrate. This review primarily introduces recent studies about microneedles on the flexible substrate, various fabrication methods of microneedles on the flexible substrate, including micromolding, silicon dry/wet etching, electrochemical etching, drawing-lithography, electro-drawing lithography, magnetorheological drawing lithography, three-dimensional printing, vapor–liquid–solid grown, hot embossing, and assembly, and corresponding materials have been summarized and discussed in details. In the end, regular biomedical applications of microneedle on the flexible substrate are categorized into drug delivery, vaccine delivery, electrophysiological interaction, sampling and bio-sensing. Recent advances of each application have been discussed.